AUDIT OF USFDA APPROVALS FOR 2022 FROM THE PERSPECTIVE OF INNOVATION - DASARAJU, RAJESH; BAPUGOUDA, PATIL; BENDE, MANOHAR; MANGALGIRI, ASHUTOSH; MUPPALA, THEJASWINI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The United States of America (USA) is having a unique place in global innovation within the health-care sector due to the presence of a large number of research-oriented biopharmaceutical companies, contract research organizations, and government research agencies. The aim of this study was to analyze the U.S. Food and Drug Administration (USFDA) approvals for 2022 to increase the awareness among health-care professionals for better clinical decisions. Methods: This was an observational study conducted using online database of USFDA which is accessible freely by the public. The USFDA approvals for 2022 were assessed for new molecular entities (NMEs) including their source and therapeutic area, new indications (NIs) of previously approved drugs, new label extensions (NLEs) of previously approved drugs, new routes of administration (NRAs) of previously approved drugs, and new dosage forms (NDFs) of previously approved drugs. The data obtained were arranged in the tabular form using Microsoft Office Excel 2007. Descriptive statistics was used for analysis. Results: Out of 118 USFDA approvals considered for this study, 25.4% of them were given for NMEs, 27.9% approvals were given for NIs, 33.8% approvals were given for NLEs, 6.7% approvals were given for NRAs, and the remaining 5.9% approvals were given for NDFs. 14 out of 30 NMEs were biologicals and 43.3% of NMEs were indicated for different types of cancer. Conclusion: The USFDA continued to adopt several approaches such as Fast Track process, breakthrough therapy process, accelerated approval process, and priority review process to encourage the research-based biopharmaceutical companies involved in the development of therapeutic options for patients suffering from common as well as rare diseases. More emphasis was given to the approvals of anticancer drugs given the limited options available to treat the cancer in advanced or metastatic stages. However, a lack of discovery and development of antimicrobials with novel mechanism of actions to combat resistance is a cause of concern.